2010
DOI: 10.1111/j.1753-318x.2010.01061.x
|View full text |Cite
|
Sign up to set email alerts
|

Urban pluvial flooding: a qualitative case study of cause, effect and nonstructural mitigation

Abstract: Historically, flood risk management in the United Kingdom has mainly concentrated on river and coastal flooding, yet flooding from surface water runoff is a risk to urban areas. A comprehensive study of the causes, the impact and the consequences as well as the management of serious pluvial flooding in Heywood, Greater Manchester, in 2004 and 2006 revealed that the victims of the floods were unprepared, ill‐informed and confused as to responsibilities before, during and after the event. Householders had to rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 19 publications
0
57
0
Order By: Relevance
“…This is because Southern cities generally have a long history of dealing with disasters and coping with the limitations in national and local governments. However, the same is not true of the North where local coping strategies are comparatively poorly developed and generally considered harmful in terms of interfering with governmental and other institutional adaptation responses (Douglas et al, 2010;Pitt, 2008). A typical example mentioned by authorities is that, during drought periods, households generally cope with water scarcity by storing water, which leads to an increased water consumption.…”
Section: The Role Of Insurance Mechanisms For Reducing Urban Disastermentioning
confidence: 99%
See 1 more Smart Citation
“…This is because Southern cities generally have a long history of dealing with disasters and coping with the limitations in national and local governments. However, the same is not true of the North where local coping strategies are comparatively poorly developed and generally considered harmful in terms of interfering with governmental and other institutional adaptation responses (Douglas et al, 2010;Pitt, 2008). A typical example mentioned by authorities is that, during drought periods, households generally cope with water scarcity by storing water, which leads to an increased water consumption.…”
Section: The Role Of Insurance Mechanisms For Reducing Urban Disastermentioning
confidence: 99%
“…In contrast to a development in a recognised river flood plain or coastal risk area, small urban catchments (such as Heywood) are unlikely to appear in flood risk maps. Therefore, after an event (such as the 2004 and 2006 floods), the insurers are likely to adopt a cautious approach to a future risk of flooding (Douglas et al, 2010;Osbourne, 2008). People's most important coping strategy, namely, risk financing through the acquisition of an insurance policy, is thus becoming less and less effective.…”
Section: The Role Of Insurance Mechanisms For Reducing Urban Disastermentioning
confidence: 99%
“…Severe pluvial floods in the UK in 2004, 2006and 2007(Pitt, 2008Coulthard and Frostick, 2010;Douglas et al, 2010) have demonstrated that local high-intensity rainfall can have large impacts on society. Another example is the heavy rainfall event of 1998 in the Netherlands, which caused around 410 million euros (1998 values) to private buildings and agriculture (Jak and Kok, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Many coastal cities are also impacted by pluvial (or surface water) and coastal flooding (Douglas et al, 2010). Pluvial flooding occurs during intense rainfall as a result of surface water runoff associated with low permeability in urban areas that may be lying above and far from coastal and river floodplains (Douglas et al, 2010).…”
Section: Methodsmentioning
confidence: 99%